RYEGRASS PASTURE ASSOCIETED WITH WINTER LEGUMES UNDER FOUR LEVELS OF FORAGE ON OFFER, IN THE SOUTHERN REGION OF PARANÁ - IDO, Oswaldo Teruyo; de MORAES, Anibal; PELISSARI, Adelino; PISSAIA, Amir; KOEHLER, Henrique Soares (Scientia Agraria, 2005)
A ryegrass pasture (Lolium multiflorum Lam.) associated with winter legumes: red clover (Trifolium pratense L.), white clover (Trifolium repens L.) and birdsfoot trefoil (Lotus corniculatus L.), submitted to four levels of herbage allowance (HA), namely 4; 8; 12 e 16 kg of dry matter (DM) 100 kg-1 of the live weight (LW), was evaluated in a randomized complete block design with two replications. The trial was carried out in July until November 1995, at the Canguiri Experimental Station Center SCA - UFPR, at Pinhais, PR with the objective of determinate four levels allowance herbage above production of Lolium multiflorum Lam. associated by three winter legumes. The put-and-take technique in a continuous grazing system with variable stocking rate was used. Different residuals dry matter/area was conditioned by the imposition of different HA. Increasing HA, caused gradual increase in residual DM ha-1. The greatest DM production occurred in the intermediates HA. Under the range of 14% of LW, associated with 3564 kg of residual DM ha-1, occurred maximum total DM production. Reducing herbage allowance increased the DM disappearance rate.